Body dysmorphic disorder in individuals requesting cosmetic surgery: A systematic review and meta-analysis. Issue 7 (July 2022) - Salari, Nader; Kazeminia, Mohsen; Heydari, Mohammadbagher; Darvishi, Niloofar; Ghasemi, Hooman; Shohaimi, Shamarina; Mohammadi, Masoud
Summary: Background: Body dysmorphic disorder (BDD) is known as a mental disorder in which a person suffers from concern and distress with the perceived defects in their appearance and subsequently can experience significant impairment in social, occupational, and interpersonal functioning. Various studies have reported different BDD prevalence rates in patients with cosmetic surgery. However, there has been no comprehensive study that has examined the results of these studies. Therefore, this study aims to determine BDD prevalence in individuals requesting cosmetic surgery in a systematic review and meta-analysis. Methods: In this review study, a search was conducted in national and international databases of Cochrane, Embase, ScienceDirect, Scopus, PubMed, and Web of Science (WoS) between 1878 and January 2020. A random-effects model was used to analyze the data, and heterogeneity of studies was examined with the I 2 index. Data analysis was done using comprehensive meta-analysis (Version 2). Results: BDD prevalence in individuals requesting cosmetic surgery in 48 articles with a sample size of 14, 913 was 19.2% (95% CI: 15.8–23%). Regarding heterogeneity based on meta-regression, a significant difference between the sample size ( p <0.001) and BDD prevalence in patients with cosmetic surgery was observed. Conclusion: The results of this study showed that BDD prevalence in individuals requesting cosmetic surgery is high. Therefore, with the provision of feedback at hospitals, appropriate interventions, such as pre-screening for body image disturbance, should be mandated.